2020
DOI: 10.1101/2020.05.28.122168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Aging Slow Wave: A Shifting Amalgam of Distinct Slow Wave and Spindle Coupling Subtypes Define Slow Wave Sleep Across the Human Lifespan

Abstract: Study ObjectivesSlow wave and spindle coupling supports memory consolidation, and loss of coupling is linked with cognitive decline and neurodegeneration. Coupling is proposed to be a possible biomarker of neurological disease, yet little is known about the different subtypes of coupling that normally occur throughout human development and aging. Here we identify distinct subtypes of spindles within slow wave upstates and describe their relationships with sleep stage across the human lifespan. MethodsCoupling … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Differences between sleep stages, differences in spindle definitions, and differences in algorithm may all in part explain these between study differences. Recent work has also suggested that fast spindles may be further subdivided into "early" fast (occur primarily on the rising phase of the slow oscillation) and "late" fast (occur primarily at or shortly after the slow oscillation peak) spindles (McConnell et al, 2020). It is plausible that late fast spindles were primarily detected in this sample, especially given recent evidence that late fast spindles are more prevalent in SWS (McConnell et al, 2020).…”
Section: Discussionmentioning
confidence: 73%
“…Differences between sleep stages, differences in spindle definitions, and differences in algorithm may all in part explain these between study differences. Recent work has also suggested that fast spindles may be further subdivided into "early" fast (occur primarily on the rising phase of the slow oscillation) and "late" fast (occur primarily at or shortly after the slow oscillation peak) spindles (McConnell et al, 2020). It is plausible that late fast spindles were primarily detected in this sample, especially given recent evidence that late fast spindles are more prevalent in SWS (McConnell et al, 2020).…”
Section: Discussionmentioning
confidence: 73%
“…Differences between sleep stages, differences in spindle definitions, and differences in algorithm may all in part explain these between study differences. Recent work has also suggested that fast spindles may be further subdivided into “early” fast (occur primarily on the rising phase of the slow oscillation) and “late” fast (occur primarily at or shortly after the slow oscillation peak) spindles (McConnell et al , 2020). It is plausible that late fast spindles were primarily detected in this sample, especially given recent evidence that late fast spindles are more prevalent in SWS (McConnell et al , 2020).…”
Section: Discussionmentioning
confidence: 99%